PRIORITIZING BUSINESS PROCESSES: A systematic review of the literature - Barros, Fernando Rufino de; Nunes, Ester Peixoto; Morais, Alline Sardinha Cordeiro (Revista Valore, 2024)
This study aims to identify the main approaches, methodologies, criteria used to prioritize processes and results of studies on Process Management in the organizational context. This is a descriptive bibliographical research, conducted using the Systematic Literature Review (SLR) method, which uses secondary data to delve deeper into a certain topic. To analyze the 22 articles selected from the Scopus database, the content analysis technique was adopted. Seven themes were identified in the introductory context: adapting BPM to the sector/need, market competitiveness, BPM as a solution, applying BPM more effectively, focusing on the customer, prioritizing to be more efficient and process reengineering. The data shows the importance of this management instrument in the sustainability of organizations. To conduct the research, the predominance of qualitative methodologies was identified, with case studies and design science research, reinforcing the practical characteristic attributed to this topic. Regarding the criteria used, three main classifications were identified that focus on complexity, general performance and process characteristics. Finally, the applied characteristic of the research suggests the need for future studies that seek to develop models with greater adaptability to different organizations.